Characteristics of abnormal post‐stent optical coherence tomography findings in hemodialysis patients. Issue 7 (27th March 2019) - Matsuhiro, Yutaka; Matsunaga‐Lee, Yasuharu; Nakamura, Daisuke; Yano, Masamichi; Yamato, Masaki; Egami, Yasuyuki; Shutta, Ryu; Sakata, Yasushi; Nishino, Masami; Tanouchi, Jun
ABSTRACT: Aim: Clinical outcomes after percutaneous coronary intervention (PCI) in hemodialysis (HD) patients are significantly worse than those in non‐HD patients. Optical coherence tomography (OCT) is a high resolution imaging modality and provides a detailed assessment of post‐interventional abnormal findings that influence worse clinical outcomes. However, little is known about the abnormal post‐stent OCT findings in HD patients. Therefore, in this study, we compared the abnormal post‐stent OCT findings between HD and non‐HD patients. Methods: One hundred thirty‐nine consecutive OCT guided PCI (21 lesions in HD patients and 118 lesions in non‐HD patients) were enrolled. We compared the post‐stent OCT findings, including the edge dissections, under expansion index (minimum stent area/mean reference area), and stent eccentricity index (minimum stent diameter/maximum stent diameter) between HD and non‐HD patients. We also compared the device‐oriented clinical events (DoCEs) at 8 months of follow up. Results: There was a significantly higher prevalence of distal edge dissections (16.7% vs. 2.8%, P = 0.011) in HD patients. HD patients had a significantly lower under expansion index (0.76 ± 0.21 vs. 0.85 ± 0.14, P = 0.029) and stent eccentricity index (0.82 ± 0.09 vs. 0.88 ± 0.18, P = 0.018). The cumulative rate of DoCEs was significantly higher in the HD patients (23.8% vs. 5.2%, P = 0.013). Conclusions: A higher prevalence of distal edge dissections, under expansion and stent eccentricity were detected by the detailed OCT findings in HD patients.